DETERMINAN INTELLECTUAL CAPITAL DISCLOSURE: PADA PERUSAHAAN INDEKS ESG LEADERS: DETERMINANTS OF INTELLECTUAL CAPITAL DISCLOSURE: ON ESG LEADERS COMPANY INDEX - Sari, Elvita Fitriana; Endah Susilowati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this research was to test and analyze the effect of managerial ownership and institutional ownership on intellectual capital performance and intellectual capital disclosure for 2020-2021. This research used a quantitative approach. The population of this research are companies that included in the ESG Leaders index. The sample of this research as much 35 companies. The analysis technique used a content analysis and Warp Pls software. The result of this research prove that managerial ownership and institutional ownership contributed to intellectual capital performance, institutional ownership also contributed to intellectual capital disclosure, but managerial ownership and intellectual capital performance can’t contributed to intellectual capital disclosure.